Strategy of KUBE FM Kuncara Lamb in Maintaining Solidarity and Group Business in The Industrial Revolution Era 4.0 - Pujiartini, Pujiartini; Purnomo, Eko Priyo; Malawani, Ajree Ducol (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2020)
Poverty has been one of the problems that are common among countries. If the government does not want debt to be more acute, then the government must place poverty alleviation as a priority. In making a poverty alleviation program, the government must consider the causes of poverty in an area. It will have different results when the application is implemented following the target program that is not on target. The empowerment of the poor through KUBE-FM is possible for the level of success. However, the failure rate to maintain group member solidarity is still high. Then the next challenge that must be faced by this KUBE group is industrial revolution 4.0, where all have implemented an automation system in production and advertising that uses the internet, such as internet media in marketing. In this  study,  the  authors  used  an  explorative  qualitative  method  to  find  out  the  KUBE-FM  Kuncara Lamb  strategy  in  maintaining  group  and  business  solidarity  in  the  Industrial  Revolution  4.0  era. The author uses miles and Huberman’s concept to analyze the data, namely, reduction, display, and concluding. KUBE-FM strategy, Kuncara Lamb, maintains group solidarity, namely: managing group dynamics that members can be an example for everyone, transparency in the budget, and maintain honesty. In facing the era of automation and the internet of things, KUBE-FM Kuncara Lamb only relies on person-to-person advertising through friendship and seminars and hard work.